2018
DOI: 10.1111/tri.13275
|View full text |Cite
|
Sign up to set email alerts
|

Liver alone or simultaneous liver-kidney transplant? Pretransplant chronic kidney disease and post-transplant outcome - a retrospective study

Abstract: The new Organ Procurement and Transplant Network/United Organ Sharing Network (OPTN/UNOS) simultaneous liver-kidney transplant (SLK) policy has been implemented. The aim of this study was to review liver transplant outcomes utilizing the new SLK policy. Liver transplant alone (LTA) and SLK patients between 2009 and 2015 were reviewed. Graft survival and post-transplant kidney function were investigated among LTA patients meeting the chronic kidney disease (CKD) criteria of the new policy (LTA-CKD group). To va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…None of the LTA patients had ESRD at 3 years 15 . Another recent study with 27 patients undergoing LTA meeting the UNOS CKD SLK criteria found a 7% risk of needing dialysis or graft loss compared to 5% in those who received SLK 16 . Additionally, the eGFR of the LTA group was worse at 1 year compared to the SLK group (48 vs 57 mL/min, P = .03).…”
Section: Discussionmentioning
confidence: 92%
“…None of the LTA patients had ESRD at 3 years 15 . Another recent study with 27 patients undergoing LTA meeting the UNOS CKD SLK criteria found a 7% risk of needing dialysis or graft loss compared to 5% in those who received SLK 16 . Additionally, the eGFR of the LTA group was worse at 1 year compared to the SLK group (48 vs 57 mL/min, P = .03).…”
Section: Discussionmentioning
confidence: 92%
“…4). One prior study estimated lower survival rates in the LTA‐ESRD group compared with SLKT, ( 18 ) although the study was performed using data from 2007 to 2014, which largely precedes the cohort currently under discussion. In contrast, a recent single‐center report of LTA performed from 2006 to 2015 suggests that the majority of LTA patients who would have been eligible for SLKT under the 2017 criteria experienced similar posttransplant graft and patient survival rates to patients with normal renal function.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Multiple studies have evaluated the outcomes of SLK versus LT alone (LTA) in patients with renal dysfunction, and these have consistently demonstrated superior graft and patient survival for SLK in recipients with longstanding CKD or on long-term hemodialysis (HD; >3 mo), high MELD scores, and those with hepatorenal syndrome. 13-17 While these studies have shown superior results for SLK in these recipient groups, predicting renal recovery following LTA still represents a significant dilemma. Several groups have attempted to devise models or identify biomarkers to predict renal dysfunction post-LT, while others have attempted to distinguish risk factors associated with futility of SLK.…”
mentioning
confidence: 99%